Global burden and health inequality of nutritional deficiencies from 1990 to 2019 - Yu, Yang; Li, Hui; Hu, Nan-xi; Wu, Xiao-hua; Huang, Xin-yi; Lin, Hong-tao; Yu, Kai-li; Li, Jin-luan (Frontiers in Nutrition, 2024)
Introduction Nutritional deficiencies (NDs) manifest in various forms and are widespread globally. However, a systematic evaluation of the epidemiology of NDs across all causes and age groups in different countries and regions has not been conducted. Materials and methods This study aimed to utilize data from the 2019 Global Burden of Disease (GBD) study to assess the burden and trends of NDs, including their incidence, prevalence, mortality, and disability-adjusted life years (DALYs). Additionally, the study evaluated health inequalities at global, regional, and national levels from 1990 to 2019. Result In 2019, the age-standardized incidence rate of NDs was 2,207.71 per 100,000 individuals (95% UI 1,863.04–2,604.67), and the age-standardized DALYs (ASR-DALYs) was 680.12 per 100,000 individuals (95% UI 507.21–894.89). Among the causes of NDs, dietary iron deficiency had the highest ASR-DALYs and exhibited minimal variation. Children under the age of 5 years faced the greatest risk of NDs. Sex disparity was evident, with males having lower rates than females. Although the gap in the burden of NDs between regions classified as poor and wealthy decreased, disparities persist. Conclusion These findings provide critical insights for the development of global health strategies aimed at mitigating NDs and may guide policymakers in implementing effective and economically viable interventions.